Unsociability and social adjustment of Chinese preschool migrant children: The moderating role of resilience - Zhu, Jingjing; Zhang, Zhenzhen; Xu, Pin; Huang, Kaiyu; Li, Yan (Frontiers in Psychiatry, 2023)
Objectives The present study examined the moderating effect of children’s resilience on the relations between unsociability and social adjustment (i.e., prosocial behaviors, peer exclusion, interpersonal skills, internalizing problems) in Chinese preschool migrant children. Methods Participants were N = 148 children (82 boys, Mage = 62.32 months, SD = 6.76) attending two public kindergartens in Shanghai, People’s Republic of China. Mothers provided ratings of children’s unsociability and resilience; teachers assessed children’s social adjustment outcomes, and children reported their receptive vocabulary. Results Unsociability was positively associated with peer exclusion and internalizing problems, and negatively associated with prosocial behaviors and interpersonal skills among Chinese preschool migrant children. Moreover, children’s resilience significantly moderated the relationship between unsociability and social adjustment. Specifically, among children with lower levels of resilience, unsociability was significantly and positively associated with peer exclusion and internalizing problems, while among children with higher levels of resilience, unsociability was not associated with social adjustment difficulties. Conclusion The current findings inform us of the importance of improving children’s resilience to buffer the negative adjustment among Chinese migrant unsociable young children. The findings also highlight the importance of considering the meaning and implication of unsociability for preschool migrant children in Chinese culture.